Multimediální výukový program (MVP) ve vzdelávání na vysokých skolách - Chalupníková, Rita (Acta medica (Hradec Kralove). Supplementum, 2004)
This article is aimed at developing of multimedia teaching programs. Authoring tool Authorware Professional for Windows is briefly described as a suited system for the developing of didactic applications. Author presents own application based on Authorware--Biophysics of perception of sound and light. At the end are also disscused benefits of multimedia teaching tools.
Keywords: biofyzika; Multimedia; multimédia; software; Biophysics; Software; počítačem řízená výuka; Computer-Assisted Instruction